Design and rationale of two phase 3 randomised controlled trials (COUGH-1 and COUGH-2) of gefapixant, a P2X3 receptor antagonist, in refractory or unexplained chronic cough. Issue 4 (2nd November 2020) - Muccino, David R.; Morice, Alyn H.; Birring, Surinder S.; Dicpinigaitis, Peter V.; Pavord, Ian D.; Assaid, Christopher; Kleijn, Huub Jan; Hussain, Azher; La Rosa, Carmen; McGarvey, Lorcan; Smith, Jaclyn A.
Background: We present study designs, dose selection and preliminary patient characteristics from two phase 3 clinical trials of gefapixant, a P2X3 receptor antagonist, in refractory chronic cough (RCC) or unexplained chronic cough (UCC). Methods: COUGH-1 (NCT03449134) and COUGH-2 (NCT03449147) are randomised, placebo-controlled, double-blind, parallel-group trials in subjects with RCC or UCC (age ≥18 years; cough duration ≥1 year; Cough Severity Visual Analogue Scale score ≥40 mm). The primary efficacy study periods are 12 weeks (40-week extension; COUGH-1) and 24 weeks (28-week extension; COUGH-2). Interventions include placebo, gefapixant 15 mg and gefapixant 45 mg (1:1:1 ratio). The primary efficacy endpoints are average 24-h cough frequency at Week 12 (COUGH-1) and Week 24 (COUGH-2). Awake cough frequency, patient-reported outcomes and responder analyses are secondary endpoints. Results: The doses of 45 mg (to provide maximal efficacy and acceptable tolerability) and 15 mg (to provide acceptable efficacy and improved tolerability) were selected based on phase 1 and 2 studies. In COUGH-1, 730 participants have been randomised and treated; 74% are female with mean age of 59 years (39% over 65 years), and mean baseline duration of cough of 11.5 years. In COUGH-2, 1314 participants have been randomised and treated; 75% are female with mean age of 58 years (33% over 65 years), and mean baseline duration of cough of 11.1 years. Conclusions: These global studies include participants with baseline characteristics consistent with previous RCC and UCC studies and will inform the efficacy and safety profile of gefapixant in the treatment of patients with RCC and UCC. This protocol describes the design of two global, phase 3 studies with >2000 participants with refractory or unexplained chronic cough, designed to confirm efficacy and safety of gefapixant, a P2X3 receptor antagonist, at doses of 45 mg and 15 mg https://bit.ly/2Xzgu74